Cover Image. Issue 4 (10th June 2018) - Laermanns, Hannes; Kirkitadze, Giorgi; May, Simon Matthias; Kelterbaum, Daniel; Opitz, Stephan; Heisterkamp, Arne; Basilaia, Giorgi; Elashvili, Mikheil; Brückner, Helmut
Abstract : The cover image, by Hannes Laermanns et al., is based on the Research Article Bronze Age settlement mounds on the Colchian plain at the Black Sea coast of Georgia: A geoarchaeological perspective, DOI:10.1002/gea.21670 .